The Effect of Addition and Soaking Duration of Jackfruit Skin Bioadsorbent On the Purification of Used Cooking Oil - Pratama, Raka Adi; Sarofa, Ulya; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Used cooking oil that has undergone repeated frying cycles experiences a significant decline in quality due to various degradation processes. The deterioration of fats during frying is primarily caused by the interaction of oil with air (oxidation), prolonged exposure to high temperatures, interaction with food materials, and the presence of burnt residues. Indicators of oil degradation include changes in color, increased viscosity, elevated levels of free fatty acids and peroxides, and a decreased iodine number. Purification of used cooking oil is essential to remove harmful degradation by-products such as water, peroxides, free fatty acids, aldehydes, and ketones. One effective and sustainable method to improve the quality of used cooking oil is adsorption using natural adsorbents. The adsorption process involves mixing the oil with an adsorbent material capable of binding and removing impurities, followed by stirring and filtration. This study aimed to evaluate the effect of adsorbent concentration and soaking time using jackfruit peel—an agricultural waste product—as a low-cost and eco-friendly adsorbent, on the physicochemical properties of used cooking oil. The research utilized a Completely Randomized Design (CRD) with two factors: the concentration of jackfruit peel adsorbent (10%, 20%, 30%) and soaking time (30, 60, and 90 minutes). Data were analyzed using ANOVA, followed by a 5% Duncan Multiple Range Test (DMRT) and the Zeleny method to identify the best treatment combination. The optimal treatment was found to be a 30% adsorbent concentration with a 90-minute soaking time, which significantly improved the quality of the used cooking oil. The results were as follows: color score of 3.75, aroma score of 3.85, clarity score of 4.00, water content of 0.39%, free fatty acid (FFA) level of 0.23%, peroxide value of 7.18 meqO?/kg, iodine value of 66.10 I?/100g, viscosity of 70.33 cP, and a smoke point of 179.20°C. Contribution to the Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and Production, SDG 3: Good Health and Well-being, SDG 13: Climate ActionSDG 9: Industry, Innovation and Infrastructure